PENINGKATAN KEMAMPUAN MENGHAFAL KOSAKATA BAHASA ARAB (MUFRODAT) DENGAN MENGGUNAKAN METODE BERNYANYI PADA SISWA KELAS IV B MADRASAH IBTIDAIYAH AL ISLAM TEMPEL SLEMAN - Luk Luk Muniroh; Umi Faizah (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This research was conducted on the basis of the background of the problem, namely the presence of students who were less enthusiastic and seemed to have no interest in participating in learning Arabic in class because of the use of the lecture method which made students bored and less interested in Arabic subjects, considering that Arabic is a foreign language. then the main capital of class IV B students in working on questions is the provision of memorization. So it is important for teachers to equip their students with the capital to work on, namely memorizing Arabic vocabulary. The aim is to find out the implementation of mufrodat learning using the singing method and to increase the ability to memorize students' Arabic vocabulary. This research method uses Classroom Action Research, data collection techniques with observation techniques, interviews and documentation. The research subjects were 26 students of grade IV B at Madrasah Ibtidaiyah Al Islam Tempel Sleman. The results showed that: 1) Implementation of learning Arabic vocabulary (mufrodat) using the singing method for students of class IV B Madrasah Ibtidaiyah Al Islam Tempel, the learning stages are as follows: a. Video song playback, b. The teacher gives a quiz about mufrodat with the help of media images, c. Students follow the mufrodat reading that the teacher mentions to the end, d. The teacher gives rewards to students who have memorized that day. 2) Improving the ability to memorize Arabic vocabulary after using the singing method in class IV B students of Madrasah Ibtidaiyah Al Islam Tempel, it can be seen from the results of the actions taken, namely in the pre-cycle there was 0%, in cycle 1 that was 46%, and in cycle 2 that was by 81%. It can be said that the achievement of the singing method was very successful at 81% in increasing the ability to memorize mufrodat of class IV B students in Arabic subjects.